Pengaplikasian Prinsip-Prinsip Green Chemistry Dalam Pelaksanaan Pembelajaran Kimia - Eva Fadillah (Pusat riset dan Inovasi Nasional, 2022)
Green chemistry studies generally include effective concepts and approaches to prevent environmental pollution caused by toxic and hazardous chemical products and processes. Green chemistry based chemistry learning becomes one of the methods that can be used as an approach to prevent pollution caused by chemicals. Laboratory activities attempt to use the principle of green chemistry that can be done by reducing, eliminating or using toxic and hazardous chemicals used in an experiment to reduce levels of pollutants and waste volumes. As educators in the implementation of chemistry learning is expected to have the knowledge, insight, and skills in applying the principles of green chemistry.